2018
DOI: 10.4081/ija.2018.1264
|View full text |Cite
|
Sign up to set email alerts
|

Residual soil nitrate as affected by giant reed cultivation and cattle slurry fertilisation

Abstract: The residual soil nitrate (RSN) is the amount of nitrate which remains in soil profile after crop uptake has ceased, typically in the autumn. The RSN is prone to leaching and therefore poses serious environmental concerns, especially in areas with intensive livestock activities. Little is known about the ability of the energy grass giant reed in leaving low RSN. Such ability would add a desirable environmental benefit to giant reed cultivation. This article reports on snapshot measurements of RSN across soil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Such study indicated that giant reed possesses high agronomic efficiency of applied nitrogen (Ceotto et al, 2015) and the ability to reduce the risk of nitrate pollution dealing with nitrogen surplus. (Ceotto et al, 2018).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Such study indicated that giant reed possesses high agronomic efficiency of applied nitrogen (Ceotto et al, 2015) and the ability to reduce the risk of nitrate pollution dealing with nitrogen surplus. (Ceotto et al, 2018).…”
Section: Methodsmentioning
confidence: 98%
“…According to D’Imporzano et al (2018) the high productivity of giant reed, combined to its low requirement of agronomic inputs, is key for minimizing the environmental impact of the crop. Moreover, giant reed exerts an effective soil nitrate removal, therefore reducing the risk of nitrate pollution (Ceotto et al, 2018). While giant reed has been largely investigated during the last decade, most of the studies focused on the crop harvested when the annual growth has ceased, notably in autumn or winter (Angelini et al, 2009; Borin et al, 2013; Cosentino et al, 2006; Monti & Zegada‐Lizarazu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when cultivating Virginia mallow [182] in marginal sandy soil, digestate fertilization resulted in significantly less N leaching compared with NPK fertilizer but similar biomass yields and an increased soil carbon content, water holding capacity, and soil basal respiration, indicating an improved fertility of the marginal soil [132,183]. Other perennial biomass crops such as giant reed have the characteristic of leaving very low amounts of residual soil nitrate after harvest, which also helps in reducing potential N leaching over winter [184]. In an intercropping system of triticale and clover grass on two marginal sites, separated digestates were able to substitute mineral fertilizer completely in a long-term experiment (longer than six years) without decreasing biomass yield [185].…”
Section: Groundwater Protection and Nutrient Recyclingmentioning
confidence: 99%
“…We did not consider in our simulation any nitrogen stress on crop growth, according to the low giant reed requirements in the study area, as partly demonstrated by negligible yield differences between fertilized and unfertilized giant reed productivity in CT field experiments [37,70]. Indeed, this species is a rhizomatous grass characterized by high mobility of nutrients between above-and belowground organs: In autumn, before harvest, part of nitrogen in aboveground organs is remobilized and stored in the rhizome, and re-used for tiller emission and growth in the next spring re-sprouting [23,71]. Where these assumptions do not hold, hence our results may be slightly overestimated; in such a case, additional data will be needed for model calibration, possibly considering experiments where giant reed biomass is collected under different fertilization strategies.…”
Section: Final Remarks and Limitations Of The Studymentioning
confidence: 88%
“…As a matter of fact, in Southern European climates, this crop can be grown in many soils, ranging from heavy clay to loose sands and gravel soils, and also tolerates both high salinity and extended periods of drought [19]. Besides its rusticity, this species can provide several ecosystems services: an outstanding biomass productivity [20]; a substantial soil carbon sequestration [21]; high nitrogen (N) use efficiency [22]; and an effective residual soil nitrate removal across soil profile [23]. Furthermore, the very deep root system allows the crop to adsorb soil pollutants, favoring soil phytoremediation and aggregation [10].…”
Section: Introductionmentioning
confidence: 99%